2009
DOI: 10.1590/s0036-36342009001000019
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of abnormal eating behaviors in adolescents in Mexico: Mexican National Health and Nutrition Survey 2006

Abstract: Objective. To describe the prevalence of abnormal eating behaviors in a population-based nationwide survey. Material and Methods. A stratified, probabilistic, multistage design sampling process was used. The Brief Questionnaire for Risky Eating Behaviors was included in the Mexican Health and Nutrition Survey 2006 (ENSANUT 2006) and administered to participants 10-19 years old (n= 25 166). The study had the power to describe nationwide characteristics by age, regions and urban/rural settings. Results. A high r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 18 publications
1
12
0
8
Order By: Relevance
“…Esses são avaliados considerando-se basicamente a presença dos sintomas clássicos dos quadros: restrição alimentar (hábito de fazer dietas restritivas ou jejum), compulsão alimentar e práticas purgativas (uso de laxantes, diuréticos e vômitos autoinduzidos) [7][8][9][10] . Diferentes nomenclaturas podem ser adotadas para avaliar esses mesmos aspectos, por exemplo, comportamento alimentar anormal 11 , suspeita de transtornos alimentares 12 , risco de transtornos alimentares 13 , comportamentos de risco para transtornos alimentares 7 , sintomas de transtornos alimentares 14 , atitudes alimentares anormais 15 , padrões alimentares anormais 16 . Outra terminologia utilizada é o "comer transtornado", definido pela Associação de Psiquiatria Americana e pela Associação Dietética Americana como todo espectro dos problemas alimentares, da "simples dieta" aos TA clássicos 1,4 .…”
Section: Introductionunclassified
“…Esses são avaliados considerando-se basicamente a presença dos sintomas clássicos dos quadros: restrição alimentar (hábito de fazer dietas restritivas ou jejum), compulsão alimentar e práticas purgativas (uso de laxantes, diuréticos e vômitos autoinduzidos) [7][8][9][10] . Diferentes nomenclaturas podem ser adotadas para avaliar esses mesmos aspectos, por exemplo, comportamento alimentar anormal 11 , suspeita de transtornos alimentares 12 , risco de transtornos alimentares 13 , comportamentos de risco para transtornos alimentares 7 , sintomas de transtornos alimentares 14 , atitudes alimentares anormais 15 , padrões alimentares anormais 16 . Outra terminologia utilizada é o "comer transtornado", definido pela Associação de Psiquiatria Americana e pela Associação Dietética Americana como todo espectro dos problemas alimentares, da "simples dieta" aos TA clássicos 1,4 .…”
Section: Introductionunclassified
“…The lifetime prevalences found were .5% for AN and 1% for BN [5]. The surveys of Drug and Alcohol Use Prevalence in Mexico City students, which collect information from high schools (grades [7][8][9][10][11][12], are another source of population data. Since 1997, those periodic surveys have been collecting information on the prevalence of DEB by means of a standardized instrument [6].…”
mentioning
confidence: 99%
“…It was found that DEB are more frequent among girls, increase with age, and are less frequent in the southern region of the country. However, that study did not specifically address the relationship between DEB and socioeconomic status (SES) [9].…”
mentioning
confidence: 99%
“…55 Also, among adolescents the emergence of abnormal eating behaviors, including binge and restrictive eating and purging, was documented. 56 It should also be noted that recently the issue of beverage consumption among the Mexican population has received increased attention. In 2008 as part of a study led by a group of nutrition experts to evaluate beverage consumption patterns concluded that caloric beverages provide more than 20% of the total energy intake of Mexican adolescents and adults.…”
Section: Discussionmentioning
confidence: 99%